ANALISIS STRATEGI PENGELOLAAN DANA ZAKAT BAGI KETAHANAN EKONOMI MASYARAKAT: (Studi kasus Badan Amil Zakat Nasional kabupaten Ngawi) - Lina Nur Anisa; Lia Fitriani (Fakultas Ekonomi Bisnis Islam, 2022)
Badan Amil Zakat Nasional (BAZNAS) Ngawi Regency is one of the Indonesianzakat amil bodies whose job is to collect zakat in Ngawi Regency. There are twotypes of zakat distribution in Ngawi Regency, namely consumptive and productive,where the distribution of zakat is defined as the distribution of zakat to mustahiqconsumptively, while the utilization of zakat is interpreted as distributing zakat tomustahiq productively. BAZNAS Ngawi Regency also has 5 programs namelyHealthy Ngawi, Smart Ngawi, Prosperous Ngawi, Caring Ngawi, and ProsperousNgawi. This research will discuss how the management system of zakat funds atBAZNAS Ngawi district, and the strategy of BAZNAS Ngawi district in buildingcommunity resilience. The purpose of this study was to find out about identifyingthe zakat fund management system for the community's economy and BAZNAS'sstrategy in building community economic resilience. The form of this study used aqualitative research method conducted at BAZNAS Ngawi Regency. The datacollection technique used in this study was by using observation, which wascarried out when carrying out the PPL program at BAZNAS Ngawi. Zakat isphysical or physical worship and mall or treasure worship. So, when viewedsociologically, zakat is a reflection of an attitude of empathy (caring) for fellowhuman beings. The benefits of this empathetic attitude are in the context ofalleviating the burden on human life from an economic and another perspective.From this concept, it can be concluded that zakat has a very strategic function inits economic system. Lembaga Pengelolaan Zakat (LPZ) is an institution taskedwith managing zakat, infaq, and shodaqoh both formed by the government such asBAZ, and formed by the community and protected by the government such as LAZ.That the management of zakat is planning, implementing, and coordinatingactivities in the collection, distribution, and utilization of zakat.